The Student Writer: Editor and Critic - Fine Clouse Barbara (McGraw -Hill, 2003)
This modes-based rhetoric/reader/handbook teaches students how to become astute critics and editors of their own writing, offering new material on argumentation, applying the patterns of organization, writing about literature, visual argument, and ethics in writing.